One Stay Three Stray in Teaching Reading - Baroroh, Maghfirotul (ELLITE, 2018)
This research aimed to know whether one stay three stray method can improvestudents’ reading comprehension at SMA Muhammadiyah 3 Jember in 2017/2018academic year. The type of this research was Classroom Action Research (CAR).This research was done in two cycles which consisted of planning, implementing,observing, and reflecting in each cycle. The subjects of this research were thestudents 32 students of tenth Science at SMA Muhammadiyah 3 Jember. Theresearch instruments used were reading test and observation checklist. Theresult of reading test data in cycle 1 showed that the students did not achieve thecriteria of success. The researcher needed to revise lesson plan or strategy in cycle2. All activities were done with the balance partner and having two clockwisearound the room. Based on result of data analysis there was improvement onstudents’ reading comprehension which can be seen from the results of the twocycles in which cycle 2 was better than cycle 1.